PRACTICAL RECOMMENDATION OF USING GENERATIVE AI IN BUSINESS - REZNIKOV, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Generative Artificial Intelligence (GenAI) is transforming the economic landscape by introducing innovative solutions that significantly enhance business efficiency, drive innovation, and create competitive advantages. This article delves into the economic implications and practical applications of GenAI across various business domains, including marketing, customer support, product design, and data analysis. By leveraging advanced AI models, companies can automate routine tasks, generate personalized content, and optimize operations, leading to substantial economic benefits. The implementation of GenAI necessitates a systematic approach, starting with business concept validation and progressing through stages of technical solution identification, proof of technology, and project planning. These stages ensure that AI solutions are economically viable, effective, and aligned with business objectives. Businesses can adopt different strategies to integrate GenAI, ranging from the rapid deployment of third-party applications to the development of customized in-house models. Each approach offers unique economic benefits, balancing customization and control with implementation time and value.This article provides practical recommendations for strategy of implementing Generative AI, emphasizing the importance of careful economic analysis, stakeholder engagement, and continuous improvement. By adopting a structured approach and selecting the appropriate integration strategy, businesses can harness the transformative power of GenAI. This enables them to innovate and thrive in an increasingly competitive economic environment, positioning themselves as leaders in the digital age.
Keywords: Business; Generative AI; Business Applications; Economic Impact; Business Strategy